2017
DOI: 10.1093/gerona/glx248
|View full text |Cite
|
Sign up to set email alerts
|

Local Klotho Enhances Neuronal Progenitor Proliferation in the Adult Hippocampus

Abstract: Klotho is an aging-related protein associated with hippocampal cognitive performance in mammals. Klotho regulates progenitor cell proliferation in non-neuronal tissues, but its role in adult hippocampal neurogenesis (AHN) has not been explored. Klotho expression in the adult mouse hippocampus was examined by immunofluorescence and PCR. AHN was evaluated in the hippocampus of klotho knock-out mice (KO), klotho KO/vitamin D-receptor mutant mice, and in a model of local klotho hippocampal knockdown. The recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Notably, this finding was only observed in the DH, the axis most implicated in cognitive processing and spatial memory [77]. Although previous studies have demonstrated that Kl is important for AHN [32,33], to our knowledge this is the first time that a gene has been proposed to regulate AHN specifically in one axis of the hippocampus. This finding is aligned with previous reports that showed Kl knockout mice exhibit impaired long-term memory recall without changes in emotionality [25,78].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Notably, this finding was only observed in the DH, the axis most implicated in cognitive processing and spatial memory [77]. Although previous studies have demonstrated that Kl is important for AHN [32,33], to our knowledge this is the first time that a gene has been proposed to regulate AHN specifically in one axis of the hippocampus. This finding is aligned with previous reports that showed Kl knockout mice exhibit impaired long-term memory recall without changes in emotionality [25,78].…”
Section: Discussionmentioning
confidence: 71%
“…We demonstrate that, with an overall 10% matched-energy intake, IF in the form of every-other-day feeding is superior to daily CR in enhancing long-term memory performance in mice, and we provide evidence that this enhancement is associated with increased AHN and expression of the longevity gene Kl. Previous studies have already implicated Kl in the regulation of the hippocampal neurogenic process to different extent depending on the age of the mice [32,33]. The human hippocampal progenitor cell line HPC0A07/03A was transduced with a lentivirus to generate a cell line named Klover that conditionally overexpressed the secreted form of KL in response to doxycycline withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that KL regulates life-extension, and derives much of its antiaging capacities from regulation of the telomerase activity in stem cells (11,12). For example, one study demonstrated that mice enjoyed extended life spans when KL was overexpressed (12,13). Conversely, KL deficiency has been shown to induce premature aging (12).…”
mentioning
confidence: 99%
“…Since it has been shown previously that overexpression of full-length α-Klotho affects neurogenesis (Zhou et al, 2018), we tested whether human secreted Klotho expressed in CA1 neurons enhances pluripotency in the SGZ (Laszczyk et al, 2017). Several transcription factors have been described that can be utilized to evaluate the state of newly developed cells (Salech et al, 2017). We used the transcription factor sex determining region Y-box 2 (SOX2) as a marker protein for pluripotent cells.…”
Section: Discussionmentioning
confidence: 99%